Saturated‐core fault current limiters for AC power systems: Towards reliable, economical and better performance application. Issue 4 (1st August 2020) - Yuan, Jiaxin; Gan, Pengcheng; Zhang, Zhaoyang; Zhou, Hang; Wei, Liangliang; Muramatsu, Kazuhiro
Abstract : With the continuous expansion of power grid capacity, the problem of short‐circuit current exceeding the standard is becoming increasingly serious. Fault current limiter is a promising solution and is gradually becoming a research hotspot. In this study, fault current limiters are classified into four categories. And saturated‐core fault current limiters are emphatically introduced, including its working principle and comparison with the other three categories. Saturated core fault current limiters are divided into four branches according to the ways leading the core saturated. A comprehensive review of the research activities and emerging technologies of saturated‐core fault current limiters for AC power systems is presented in this study. The working principle and typical structure of DC‐biased‐, permanent‐magnet‐, superconducting‐ and hybrid‐type saturated‐core fault current limiters are introduced. The advantages and disadvantages of four types of saturated core fault current limiters are compared in detail from the aspects of current‐limiting performance, iron core size and DC magnetomotive force. Real grid application examples of some types of devices are presented, as well as new progress in the techniques, are covered and discussed in detail. One may find the content of this study helpful as a detailed literature review or as practical technical guidance.